Unmasking Student Struggles: Speaking Challenges at UIN Mataram's English Study Club - Khairun Nisya Naam; Kasyfur Rahman (Institut Agama Islam Negeri Kerinci, 2023)
Speaking skills are imperative to master when learning English and become one of the challenges for students who join the English Study Club (ESC). ESC, an extracurricular community for English language learning under the auspices of the State Islamic University of Mataram, provides an ideal platform for students to enhance their speaking abilities. This study aims to identify the problems students experience in learning to speak English and the factors that contribute to their difficulties. Using a qualitative descriptive approach, this study utilizes observations and interviews to gather relevant data. The findings reveal three primary challenges faced by students in learning to speak English: inhibition, low or uneven participation, and the use of their native language. Furthermore, two factors are identified as causing difficulties in students' English speaking skills: insufficient mastery of vocabulary and grammar.